2015
DOI: 10.5194/gmd-8-3179-2015
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of atmospheric N<sub>2</sub>O with GEOS-Chem and its adjoint: evaluation of observational constraints

Abstract: Abstract. We describe a new 4D-Var inversion framework for nitrous oxide (N2O) based on the GEOS-Chem chemical transport model and its adjoint, and apply it in a series of observing system simulation experiments to assess how well N2O sources and sinks can be constrained by the current global observing network. The employed measurement ensemble includes approximately weekly and quasi-continuous N2O measurements (hourly averages used) from several long-term monitoring networks, N2O measurements collected from d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 57 publications
2
28
0
Order By: Relevance
“…This has the advantage of avoiding any aggregation errors associated with traditional clustering methods. However, our previous work (Wells et al, 2015) has shown that the degrees of freedom for atmospheric N 2 O inversions is typically much less than the native model grid dimension and, furthermore, that native resolution optimizations have limited ability to resolve any temporal (e.g., seasonal) N 2 O emission biases. We therefore apply two alternate approaches to reduce the dimension of the inverse problem: (1) a 4D-Var inversion solving for emissions on aggregated, geographically defined land and ocean regions and (2) a 4D-Var inversion solving for emissions on a reduced emission basis set defined using an SVD-based information content analysis.…”
Section: Inversion Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…This has the advantage of avoiding any aggregation errors associated with traditional clustering methods. However, our previous work (Wells et al, 2015) has shown that the degrees of freedom for atmospheric N 2 O inversions is typically much less than the native model grid dimension and, furthermore, that native resolution optimizations have limited ability to resolve any temporal (e.g., seasonal) N 2 O emission biases. We therefore apply two alternate approaches to reduce the dimension of the inverse problem: (1) a 4D-Var inversion solving for emissions on aggregated, geographically defined land and ocean regions and (2) a 4D-Var inversion solving for emissions on a reduced emission basis set defined using an SVD-based information content analysis.…”
Section: Inversion Frameworkmentioning
confidence: 99%
“…The N 2 O simulation employed here, previously described by Wells et al (2015), is based on the GEOS-Chem CTM (www.geos-chem.org) with GEOS-5 assimilated meteorological data from the NASA Goddard Earth Observing System. We use a horizontal resolution of 4 • × 5 • with 47 vertical levels from the surface to 0.01 hPa as well as time steps of 30 min for transport and 60 min for emissions and chemistry.…”
Section: Geos-chem N 2 O Simulationmentioning
confidence: 99%
See 3 more Smart Citations